PILOT TESTING OF THE UNIVERSAL QUESTIONNAIRE IN PRIMARY HEALTH CARE SETTINGS - У. А. Худайбергенов; Ш. А. Аббосов; А. А. Оллоёров (Galaxy International Interdisciplinary Research Journal, 2023)
Urological diseases have a significant impact on the health of society [2,4]. Determining the true prevalence of urological diseases requires an assessment of the so-called latent urological morbidity ("urological iceberg") [3]. To solve this problem, it is more informative to conduct a targeted survey of the population, rather than an analysis of data on their use of medical care. This is due to the fact that the circulation rate depends on many factors, such as the development of infrastructure and medical care, its accessibility, general and medical culture, habits, customs and mentality of the population, which affect its medical activity. In the light of the implementation of the tasks set by the State Program for Reforming the Health Care System [1], the development of simple and affordable methods of diagnosis and optimal methods of conservative treatment of urological patients and, importantly, their introduction into the primary health care environment, training general practitioners in the ability to recognize persons with urological diseases and identify those who need treatment are in particular demand.